Ultrasound-assisted extraction for the determination of α-linolenic and linoleic acid in vegetable oils by high performance liquid chromatography - Gonzales-Condori, Elvis Gilmar; Alvarez-Gonzales, Rosa; Ramírez-Revilla, Stamber Alvaro (Eclética Química, 2021)
The present research consisted in determining α-linolenic acid (ALA, ω-3) and linoleic acid (LA, ω-6) in vegetable oils with ultrasound-assisted extraction. The analytical method was validated by high performance liquid chromatography (HPLC) for the quantification of both polyunsaturated fatty acids (PUFA). The determination was made at a wavelength of 205 nm, mobile phase composed of acetonitrile: methanol: acetic acid 1% (85:5:10), with a flow of 1 mL min-1 and during 5 min. The calibration graph data (50 to 300 mg L-1) adjusted to the linear regression model with a coefficient of determination (R2) of 0.99914 and 0.99986 for ALA and LA, respectively. The repeatability, reproducibility, accuracy and percentage of recovery complied with international guidelines for analytical methods. The proposed method is simple, fast, linear, precise and accurate for the quantitative determination of ALA and LA in vegetable oils. The previous ultrasound application during 10 min achieves significantly higher concentrations (p < 0.05) when ultrasound is not applied. In conclusion, the present method can serve as a useful alternative for routine determinations of ALA and LA in vegetable oils, as it proved to be an easy, fast and reliable method.